Chloroplast Genomes of the Green-Tide Forming Alga Ulva compressa: Comparative Chloroplast Genomics in the Genus Ulva (Ulvophyceae, Chlorophyta) - Liu, Feng; Melton, James T. (Frontiers in Marine Science, 2021)
To understand the evolution of Ulva chloroplast genomes at intraspecific and interspecific levels, in this study, three complete chloroplast genomes of Ulva compressa Linnaeus were sequenced and compared with the available Ulva cpDNA data. Our comparative analyses unveiled many noticeable findings. First, genome size variations of Ulva cpDNAs at intraspecific and interspecific levels were mainly caused by differences in gain or loss of group I/II introns, integration of foreign DNA fragments, and content of non-coding intergenic spacer regions. Second, chloroplast genomes of U. compressa shared the same 100 conserved genes as other Ulva cpDNA, whereas Ulva flexuosa appears to be the only Ulva species with the minD gene retained in its cpDNA. Third, five types of group I introns, most of which carry a LAGLIDADG or GIY-YIG homing endonuclease, and three of group II introns, usually encoding a reverse transcriptase/maturase, were detected at 26 insertion sites of 14 host genes in the 23 Ulva chloroplast genomes, and many intron insertion-sites have been found for the first time in Chlorophyta. Fourth, one degenerate group II intron previously ignored has been detected in the infA genes of all Ulva species, but not in the closest neighbor, Pseudoneochloris marina, and the other chlorophycean taxa, indicating that it should be the result of an independent invasion event that occurred in a common ancestor of Ulva species. Finally, the seven U. compressa cpDNAs represented a novel gene order which was different from that of other Ulva cpDNAs. The structure of Ulva chloroplast genomes is not conserved, but remarkably plastic, due to multiple rearrangement events.